A history of Canadian legal thought : collected essays - Risk, R. C. B., 1936- (Osgoode Society for Canadian Legal History., 2006)
Written over more than two decades, and covering the immediate post-Confederation period to the 1960s, these essays reveal a distinctive Canadian tradition of thinking about the nature and functions of law, one which Risk clearly takes pride in and urges us to celebrate.